1996
DOI: 10.4012/dmj.15.11
|View full text |Cite
|
Sign up to set email alerts
|

Surface Contamination of Titanium by Abrading Treatment

Abstract: This study investigated the contamination of abraded Ti surfaces. Using a polishing machine, specimens were abraded with waterproof SiC grit papers under water cooling. The abraded surfaces were examined using element analysis, X-ray diffraction, and hardness tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 3 publications
0
28
1
Order By: Relevance
“…In other words, the characteristics of the Ti surface play a key role in its biocompatibility. Most of the surfaces of cast and polished Ti have a reactive and contaminated layer [5][6][7][8][9] . It was assumed that these layers which form on the Ti surface influence the biocompatibility and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the characteristics of the Ti surface play a key role in its biocompatibility. Most of the surfaces of cast and polished Ti have a reactive and contaminated layer [5][6][7][8][9] . It was assumed that these layers which form on the Ti surface influence the biocompatibility and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction of the abraded surface was performed to identify the contaminants. It was reported that (1) the contamination of titanium was related to its reactivity as well as its hardness, (2) in spite of water cooling and slow-speed abrading, titanium surfaces were obviously contaminated, (3) contaminant deposits with dimensions ranging from about 10 to 30 μm occurred throughout the surfaces, and (4) the contaminant of titanium, although related also to the hardness, resulted primarily from a reaction with abrasive materials, and such contamination could negatively influence titanium's resistance to corrosion and its biocompatibility [81].…”
Section: Sandblastingmentioning
confidence: 99%
“…Miyakawa et al [81] studied the surface contamination of abraded titanium. Despite low grinding speeds and water cooling, the abraded surfaces were found to be contaminated by abrasive constituent elements.…”
Section: Sandblastingmentioning
confidence: 99%
“…The high quality of osteointegration facilitates an accelerated healing process of traumatized bone and ensures high stability and durability of implants. In order to decrease osteo-integration period or to improve the quality of implants, hydroxyapatite (HA) compound can be deposited on a metallic material as a thin * E-mail: nicanornick@yahoo.com layer [1]. Surface modifications in order to deposit thin films are generally divided into two categories: a concave and a convex texturing.…”
Section: Introductionmentioning
confidence: 99%